2017
DOI: 10.3390/f8030054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Textural Differentiations in Forest Resources in Romania Using Fractal Analysis

Abstract: Deforestation and forest degradation have several negative effects on the environment including a loss of species habitats, disturbance of the water cycle and reduced ability to retain CO 2 , with consequences for global warming. We investigated the evolution of forest resources from development regions in Romania affected by both deforestation and reforestation using a non-Euclidean method based on fractal analysis. We calculated four fractal dimensions of forest areas: the fractal box-counting dimension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 46 publications
(86 reference statements)
0
33
0
Order By: Relevance
“…between individual regions within one country (Andronache et al 2017). The variability in forest cover among countries and administrative regions results from different political settings, socioeconomic conditions, ownership structure and management practices in the past and present (Cvitanovic et al 2016, Andronache et al 2017. At a global level, Keenan et al (2015) revealed that forest cover increases with the increasing income of the region or the country, while Crespo Cuaresma et al (2017) revealed a U-shaped relationship between the income per capita and the forest cover of countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…between individual regions within one country (Andronache et al 2017). The variability in forest cover among countries and administrative regions results from different political settings, socioeconomic conditions, ownership structure and management practices in the past and present (Cvitanovic et al 2016, Andronache et al 2017. At a global level, Keenan et al (2015) revealed that forest cover increases with the increasing income of the region or the country, while Crespo Cuaresma et al (2017) revealed a U-shaped relationship between the income per capita and the forest cover of countries.…”
Section: Introductionmentioning
confidence: 99%
“…In general, large differences in forest cover as well as in hectare stock exist not only between individual countries but also at intracountry level, i.e. between individual regions within one country (Andronache et al 2017). The variability in forest cover among countries and administrative regions results from different political settings, socioeconomic conditions, ownership structure and management practices in the past and present (Cvitanovic et al 2016, Andronache et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In the analyses, we used images classified into forested areas (annually 2000-2014), for deforested areas (annually 2001-2014) and the reforested areas only a single synthetic image from 2001 to 2014 (a single image containing all the regeneration from 2001-2014) [37]. We have processed these TIFF encoded time series of Landsat images (Table 1) to extract deforested and reforested areas as described in more details in [34]. Subsequently, images were transformed into binary images using default binary function from ImageJ 1.51 software [38] and analyzed using a macro for calculating the area and the percentage of forest pixels ( Figure S1 in Supplementary Materials).…”
Section: Preprocessing Algorythm Of the Satelite Images For Analysingmentioning
confidence: 99%
“…Because the shapes of forest areas are morphologically complex, fragmented, uneven and because standard descriptors depend on the scale of observation [32], we propose an invariant scale analysis as fractal analysis. The utility of fractal analysis in forest research was demonstrated previously by our research team [31,33,34]. Fractal analysis is a powerful tool both for describing irregular objects in nature because they cannot be defined by classical Euclidean geometry [35] and for measuring seemingly random or too complex patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation